Current Practices in Hyaluronic Acid Dermal Filler Treatment in Asia Pacific and Practical Approaches to Achieving Safe and Natural-Looking Results - Corduff N; Juniarti L; Lim TS; Lin F; Mariwalla K; Pavicic T; Quiambao A; Siew TW; Suwanchinda A; Tseng FW; Vachiramon V; Youn CS; et al. (Dove Medical Press, 2022)
Niamh Corduff,1 Lanny Juniarti,2 Ting Song Lim,3 Frank Lin,4 Kavita Mariwalla,5 Tatjana Pavicic,6 Arnelle Quiambao,7 Tuck Wah Siew,8 Atchima Suwanchinda,9,10 Fang Wen Tseng,11 Vasanop Vachiramon,10 Choon Shik Youn,12 Wilson WS Ho13 1Cosmetic Refinement Clinic Geelong, Victoria, Australia; 2Miracle Aesthetic Clinic, Surabaya, Indonesia; 3Clique Clinic, Kuala Lumpur, Malaysia; 4Eastern Plastic Surgery, Victoria, Australia; 5Mariwalla Dermatology, New York, NY, USA; 6Private Practice for Dermatology & Aesthetics of Dr. Tatjana Pavicic, Munich, Germany; 7YouPlus Intelligent Aesthetics Clinic, BGC Taguig City, Philippines; 8Radium Medical Aesthetics, Singapore; 9Department of Medicine, Chulabhorn Hospital, Chulabhorn Royal Academy, Bangkok, Thailand; 10Division of Dermatology, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 11Milano Aesthetic Clinic, Taoyuan City, Taiwan; 12Yemiwon Dermatologic Clinic, Seoul, Korea; 13The Specialists: Lasers, Aesthetic & Plastic Surgery, Central, Hong KongCorrespondence: Niamh Corduff, Cosmetic Refinement Clinic Geelong, T9 400 Pakington St, Newtown VIC, Victoria, 3220, Australia, Tel +61 407122578, Email niamh.crc@outlook.comAbstract: Complications such as delayed inflammatory reactions (DIRs) and unnatural outcomes can sometimes arise from hyaluronic acid (HA) dermal filler treatments and can be challenging to address. Given the popularity of HA dermal fillers for aesthetic procedures, there is a need for preventive strategies to minimize these complications. Two hundred practitioners from 10 regions in Asia Pacific who administer HA fillers completed a survey on prevention of DIRs and unnatural outcomes. Thirteen global experts convened to evaluate the current practices and propose practical approaches for safe and appropriate use of HA dermal fillers. From the survey, the top three measures used to reduce the risk of DIRs included choosing an appropriate HA filler, aseptic technique, and patient selection. Key strategies employed to achieve natural-looking outcomes were treatment customization, understanding the rheological properties and behavior of different HA fillers, and being conservative in treatment approach. The panel developed a concise reference guide aimed at minimizing the risk of DIRs while achieving natural aesthetic outcomes. Five practical considerations were recommended: patient assessment and individualization of treatment plan, choice of an appropriate HA filler, adequate knowledge of facial anatomy, strict adherence to aseptic methods, and proper injection technique. The panel highlighted the need for education efforts to increase awareness of differential immunogenicity between HA fillers and to improve understanding on the importance of preserving aesthetic individuality for optimal results. These practical insights from the global experts support practitioners in optimizing safety and quality of aesthetic treatment with HA fillers.Keywords: hyaluronic acid dermal filler, consensus, practical approaches, safe, natural-looking outcomes, current practices